Self-reported cumulative medical opioid exposure and subjective responses on first use of opioids predict analgesic and subjective responses to placebo-controlled opioid administration. Issue 1 (January 2019) - Bruehl, Stephen; Stone, Amanda L; Palmer, Cassandra; Edwards, David A; Buvanendran, Asokumar; Gupta, Rajnish; Chont, Melissa; Kennedy, Mary; Burns, John W
Abstract : Background and objectives: To expand the evidence base needed to enable personalized pain medicine, we evaluated whether self-reported cumulative exposure to medical opioids and subjective responses on first opioid use predicted responses to placebo-controlled opioid administration. Methods: In study 1, a survey assessing cumulative medical opioid exposure and subjective responses on first opioid use was created (History of Opioid Medical Exposure (HOME)) and psychometric features documented in a general sample of 307 working adults. In study 2, 49 patients with chronic low back pain completed the HOME and subsequently rated back pain intensity and subjective opioid effects four times after receiving saline placebo or intravenous morphine (four incremental doses) in two separate double-blinded laboratory sessions. Placebo-controlled morphine effects were derived for all outcomes. Results: Two HOME subscales were supported: cumulative opioid exposure and euphoric response, both demonstrating high test–retest reliability (Intraclass Correlation Coefficients > 0.93) and adequate internal consistency (Revelle's Omega Total = 0.73–0.77). In study 2, higher cumulative opioid exposure scores were associated with significantly greater morphine-related reductions in back pain intensity (p=0.02), but not with subjective drug effects. Higher euphoric response subscale scores were associated with significantly lower overall perceived morphine effect (p=0.003), less sedation (p=0.04), greater euphoria (p=0.03) and greater desire to take morphine again (p=0.02). Discussion: Self-reports of past exposure and responses to medical opioid analgesics may have utility for predicting subsequent analgesic responses and subjective effects. Further research is needed to establish the potential clinical and research utility of the HOME. Trial registration number: NCT02469077.